2013
DOI: 10.1007/s00125-013-3059-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of type 2 diabetes in women with a history of gestational diabetes using a genetic risk score

Abstract: In women with GDM, who are at high risk of diabetes, the wGRS was significantly associated with the future development of diabetes. Furthermore, it improved prediction over clinical risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 28 publications
3
53
1
1
Order By: Relevance
“…Our previous investigation has shown that women with Japanese GDM have beta cell dysfunction irrespective of presence or absence of overweight [25]. Regarding the genetic background, several studies revealed risk variants related to insulin secretion in Korean and Chinese population [36][37][38][39][40][41]. Of the three genetic variants found in this study, two are related to the regulation of insulin secretion (i.e.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Our previous investigation has shown that women with Japanese GDM have beta cell dysfunction irrespective of presence or absence of overweight [25]. Regarding the genetic background, several studies revealed risk variants related to insulin secretion in Korean and Chinese population [36][37][38][39][40][41]. Of the three genetic variants found in this study, two are related to the regulation of insulin secretion (i.e.…”
Section: Discussionsupporting
confidence: 48%
“…Since women with GDM are at a high risk of future T2DM, genetic information on GDM would be useful for the T2DM risk classification [38,41]. Further research using a larger cohort is warranted for better understanding the genetics of GDM in Japanese women.…”
Section: Discussionmentioning
confidence: 99%
“…2) [36]. Kwak et al [58] generated a genetic risk score (GRS) that consists of 48 genetic variants associated with type 2 diabetes and validated that adding GRS to clinical models significantly increased the predictability of postpartum diabetes among 395 Korean women with previous GDM (net reclassification index 0.430, p = 7.0 × 10 –5 ). To our knowledge, no genome-wide association study has been conducted to discover specific genetic variants related to postpartum diabetes in women with previous GDM.…”
Section: Risk Factors For Postparum Diabetesmentioning
confidence: 99%
“…23 Similar findings were reported in a cohort of East Asian women using a 48-locus GRS; adding this GRS increased the C-statistic from 0.741 to 0.775 ( P = 0.02), with a continuous NRI of 0.430, indicative of moderate reclassification compared with the clinical model that included age, BMI, family history of T2DM, blood pressure and fasting levels of glucose and insulin. 24 Thus, including genetic risk in a prediction model could inform T2DM prediction even among populations already known to be at very high risk of developing this condition.…”
Section: Genetic Prediction Of T2dm Riskmentioning
confidence: 99%